APPLICATION OF ONLINE LEARNING MODELS IN AIRCRAFT COMPONENT MACHINING AT VOCATIONAL HIGH SCHOOL - Akhmad Fauzi, Ari; Hadian Sasmita, Asep; Sukrawan, Yusep (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
Covid-19 cases spread throughout the world. This Covid-19 case has disturb to all aspects of life, even the education sector has been affected. The government’s efforts to continue the learning process with distance learning (online)  as known as online learning. Expansion of this technology has begun to be used by several schools in Indonesia to implementation of their educational programs, as known as e-learning. One of them is using LMS Moddle. LMS Moddle supports to submit of learning materials, assessment, collaboration and interaction between teacher and student. Aircraft Component Machining subject were delivered by distance learning model in Vocational High School. This study aims to determine improvement of student learning outcomes with the application of online learning models. The design of this study uses Quasi-Experimental Design with Equivalent Time Series types. The research sample was 30 students from class XI Vocational High School at Bandung. The application of the syntax of the online learning model contains five steps of the learning process, namely performance support materials, self-paced learning, live events, collaboration, and assessment. The results of the study based on average value of N-gain showed that student learning outcomes had increased. User response online learning models are include in interesting category.